Prevalence, characterization and antibiotic resistance of Salmonella isolates in large corvid species of europe and north America between 2010 and 2013 - Janecko, N; Čížek, Alois; Halová, Dana; Karpíšková, Renáta; Myšková, Petra; Literák, Ivan (Zoonoses and Public Health, 2015)
It is well understood that Salmonella is carried by animals and in majority of cases as asymptomatic hosts. Surveillance efforts have focused on the role of agriculture and contamination points along the food chain as the main source of human infection; however, very little attention has been paid to the contribution of wildlife in the dissemination of Salmonella and what effect anthropogenic sources have on the circulation of antibiotic resistant Salmonella serovars in wildlife species. A purposive survey was taken of large corvids roosting yearly between November and March in Europe and North America. Two thousand and seven hundred and seventy-eight corvid faecal specimens from 11 countries were submitted for Salmonella spp. culture testing. Presumptive positive isolates were further serotyped, susceptibility tested and analysed for antibiotic resistance genes. Overall, 1.40% (39/2778) (CI = 1.01, 1.90) of samples were positive for Salmonella spp. Salmonella Enteritidis was the most prevalent serovar followed by S. Infantis, S. Montevideo and S. Typhimurium. No significant difference (P > 0.05) was found in the proportion of Salmonella recovered in Europe versus North America. The most variability of serovars within a site was in Kansas, USA with five different serovars recovered. European sites were significantly more likely to yield Salmonella resistant to more than one antibiotic (OR 71.5, P < 0.001, CI = 3.77, 1358) than North American sites, where no resistance was found. Resistance to nalidixic acid, a quinolone, was recovered in nine isolates from four serovars in four different sites across Europe. Large corvids contribute to the transmission and dissemination of Salmonella and resistance genes between human and animal populations and across great distances. This information adds to the knowledge base of zoonotic pathogen prevalence and antibiotic resistance ecology in wild birds.
Keywords: Animals; Europe; feces; Feces; Prevalence; mikrobiální testy citlivosti; salmonelóza; Salmonella Infections; lidé; Evropa; nemoci ptáků; salmonelová infekce u zvířat; bakteriální léková rezistence; Crows; Bird Diseases; prevalence; Microbial Sensitivity Tests; North America; vrány; Severní Amerika; Salmonella Infections, Animal; zvířata; Salmonella; Drug Resistance, Bacterial; Humans